KAJIAN ETNOMATEMATIKA PADA PEMBUATAN TENUN IKAT KABUPATEN SINTANG - Haura Sekarndary; Ade Mirza; Dian Ahmad BS (Universitas Tanjungpura, 2022)
Tenun ikat is one of the traditional crafts of the Sintang Dayak community, which is often made by Dayak women from generation to generation from a young age to old age. Tenun ikat is used in traditional activities, weddings, and so on. This study aims to examine the philosophy of Tiang Belumbah motifs and Pelangka motifs, ethnomathematical activities, and mathematical concepts contained in tenun ikat in the Sintang district. The research method used in this study is a qualitative method with an ethnographic approach. Data was obtained by using interview and documentation methods. The subjects in this study were the women of the village Dayak tribe who made ikat in Ensaid Panjang Village, Kelam Permai District, Sintang Regency. Based on data analysis, it was found that the philosophy of the Tiang Belumbah motif symbolizes security and the Pelangka motif symbolizes prosperity, the ethnomathematical activities identified in Sintang district tenun ikat are explaining, counting, measuring, and designing. While the mathematical concepts contained in tenun ikat are flat shapes, transformation geometry, simple graphs, and special regular graphs.